PEMIKIRAN FEMINIS MUSLIM DI INDONESIA TENTANG FIQH PEREMPUAN - M. Noor Harisuddin (IAIN Ponorogo, 2015)
Abstract: In the last three decades, there has been a transformation of society from a patriarchal society towards gender equality in Indonesia. Dissent on sex and gender has been increasing in the hands of Indonesian Muslim feminist thinkers. Sex and gender distinction between man and women as a nature of God on the one hand and gender as a cultural construct on the other hand gave rise to at least three mainstreams of thought of feminist Muslims in Indonesia; sex and gender are coextensive, women are human females, men are human males. Through gender-based realm of women fiqh (jurisprudence), this study tried to explore the Indonesian Muslim mainstream feminist thought related to gender equity. Through a number of data scattered in a number of works that appeared in three Muslim feminists of Indonesia, namely, Ratna Megawangi, Husayn Muhammad, and Muchith Muzadi, it could be illustrated that, firstly, sex and gender were two things in common or in other word the distinction between sex and gender turns out to be no distinction at all. It meant that the distinction of men to women was natural which was in Islam called ‘sunnat Allah’ and the ‘equality’ should be interpreted as ‘sunnat Allah’ too; secondly, both sex and gender are two different things, the former was the nature of God, while the latter was the result of cultural constructs so that each should be seated in its own respective positions through new perspectives far beyond the perspective of classical scholars; thirdly, although there was distinction between sex and gender, they should be positioned in their respective places without denying the perspective of classical scholars الملخص :في العقود الثلاثة الماضية، كان هناك تحول المجتمع على نطاق واسع في إندونيسيا. أي الناس الذي يرأسهم سابقا المجتمع الأبوي بين الجنسين. ومن المثير للاهتمام ، شارك الإسلام - وهو دين الأغلبية في إندونيسيا - في عملية هذا التحول . وهناك عدد كثير من المفكرين النسوي الإسلامي في إندونيسيا مع مجموعة من الأفكار المختلفة ، ولكن لا يزال مع الالتزام نفسه ، وهي لرفع كرامة المرأة في إندونيسيا . و شاركت نظرية فقه النساء من جزء